In vivo analysis of a gain-of-function mutation in the Drosophila eag-encoded K+ channel. - Cardnell, R.J.; Dalle Nogare, D.E.; Ganetzky, B.; Stern, M. (Genetics, 2006)
Neuronal Na+ and K+ channels elicit currents in opposing directions and thus have opposing effects on neuronal excitability. Mutations in genes encoding Na+ or K+ channels often interact genetically, leading to either phenotypic suppression or enhancement for genes with opposing or similar effects on excitability, respectively. For example, the effects of mutations in Shaker (Sh), which encodes a K+ channel subunit, are suppressed by loss-of-function mutations in the Na+ channel structural gene para, but enhanced by loss-of-function mutations in a second K+ channel encoded by eag. Here we identify two novel mutations that suppress the effects of a Sh mutation on behavior and neuronal excitability. We used recombination mapping to localize both mutations to the eag locus, and we used sequence analysis to determine that both mutations are caused by a single amino acid substitution (G297E) in the S2-S3 linker of Eag. Because these novel eag mutations confer opposite phenotypes to eag loss-of-function mutations, we suggest that eag(G297E) causes an eag gain-of-function phenotype. We hypothesize that the G297E substitution may cause premature, prolonged, or constitutive opening of the Eag channels by favoring the "unlocked" state of the channel.